Tensile and fracture behaviour of PP/wood flour composites - Pérez, Ezequiel (2012)
Polypropylene/wood flour composites with different fibre content were prepared. The effect of composition and the incorporation of maleinated polypropylene on the materials tensile and fracture and failure behaviour was investigated. Reliable fracture toughness data that will be useful for structural applications were obtained. In unmodified composites an increase in Young’s modulus was found with the addition of wood flour to PP, whereas tensile strength, strain at break and fracture toughness were observed to decrease as fibre content increased. The presence of MAPP was beneficial to tensile strength and ductility and had no significant effect on fracture toughness, as a result of enhanced fibre dispersion within the matrix and improved interfacial adhesion. Although reduced ductility and toughness were observed for the composites respect to the matrix, in the case of modified composites, environmentally friendly stiffer materials were obtained with cost saving without sacrificing strength.